2020
DOI: 10.1021/acs.macromol.0c00617
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorine-Containing Polymers by Functionalization of cis-1,4-Polyisoprene with Hypervalent Iodine Compounds

Abstract: Hypervalent (HV) iodine­(III) compounds with fluorine-containing ligands (F, CF3, C6F5CO2, or CF3(CF2)8CO2 (n-C9F19CO2)) reacted, in the presence of iodine or copper salts, with the double bonds in cis-1,4-polyisoprene (polyIP) to afford fluorine-containing polymers. For instance, fast iodo-fluorination of polyIP was accomplished in the presence of 4-(difluoroiodo)­toluene (4-TolIF2) and iodine. The reaction of polyIP with 1-trifluoromethyl-1,2-benziodoxol-3­(1H)-one (Togni reagent II) and copper­(I) iodide un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…To the best of our knowledge, this is the highest value to date for a water-repelling conductive polymer. We must say that another uorinecontaining polymer was investigated and its water contact angle was 116 , as reported by Tsarevsky et al 24 A high water contact angle for a non-uorinated polymer was measured by E. Lindner et al for a hydrophobic derivative of poly (3,4ethylenedioxythiophene), and it was 136 AE 5 . 6 The static water contact angle measurements reveal that by changing the deposition duration we can tune the water contact angle of the peruorinated lms from 120 to 140 .…”
Section: Resultsmentioning
confidence: 79%
“…To the best of our knowledge, this is the highest value to date for a water-repelling conductive polymer. We must say that another uorinecontaining polymer was investigated and its water contact angle was 116 , as reported by Tsarevsky et al 24 A high water contact angle for a non-uorinated polymer was measured by E. Lindner et al for a hydrophobic derivative of poly (3,4ethylenedioxythiophene), and it was 136 AE 5 . 6 The static water contact angle measurements reveal that by changing the deposition duration we can tune the water contact angle of the peruorinated lms from 120 to 140 .…”
Section: Resultsmentioning
confidence: 79%
“…[24][25][26][27] On the other hand, much attention has been given to the introduction of C F bonds by many researchers due to the low polarizability and increased free volume. 20,[28][29][30][31] Cheng et al 19 reported that epoxy reinforced with tetrafluorophenyl (FEP) displayed excellent thermal stability, and improved dielectric properties. In summary, fluoropolymers are widely used in cutting-edge fields because of their outstanding thermal properties, dielectric properties, and chemical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to modify polydienes utilizes olefin transposition reactions to retain backbone unsaturation. [37] For example, treatment with triazolinediones [33,[38][39][40] or hypervalent iodine compounds [41] affords functionalized polydienes, albeit with concomitant alkene migration. Because microstructure in unsaturated polymers can influence physical properties, [42][43][44] it would be advantageous to retain the original 1,4-diene microstructure following upcycling.…”
mentioning
confidence: 99%